The Development of an Ethnobotanical Pocketbook on Traditional Games in Kapuas Hulu Regency - Winda Rahman; Hanum Mukti Rahayu; Ahmad Faisal Amri (Jurnal Penelitian Pendidikan IPA, 2025)
This research aims to develop an ethnobotanical pocketbook based on traditional games from Kapuas Hulu Regency as a learning medium for biodiversity material in Year 10 at SMA Negeri 1 Suhaid. The method used is Research and Development (R&D) with a modified 4D model, namely define, design, and develop. The research instruments consisted of interview sheets, expert validation sheets for content, media, and language, as well as student response questionnaires. Interview data were analysed descriptively, while expert validation and practicality data were analysed using percentage formulas. The results of expert validation were 88.53% for content experts (very valid category), 87.02% for language experts (very valid category), and 86.54% for media experts (very valid category). The large-scale trial yielded an average score of 92.6%, while the small-scale trial resulted in an average score of 92.19%, both of which fall into the category of highly practical. Based on the findings, the locally-based ethnobotanical pocketbook developed is categorised as very valid and practical for use in biology learning on biodiversity topics.